ASPECTS OF THE WEAR OF SOME MATERIALS USED IN DENTISTRY - Adina Oana Armencia; Doriana Agop Forna; Irina Grădinaru; Loredana Hurjui; Vlad Dănilă; George Morărașu; Cătălina Morărașu; Daniela Onisoru; Carina Balcos (Romanian Society of Oral Rehabilitation, 2022)
Physico-chemical degradation of the dental substance is a significant event that can occur during interocclusal activities. Aim: The intention of this study is to provide as accurate data as possible, with the aim of facilitating possible comparisons between physiognomic dental biomaterials. Material and methods: The material used to investigate the tribological behavior is ceramic (VITA In-Ceram, VITA VM 13). For the experimental tests, a simulator was imagined based on some anthropometric measurements, in which the models were mounted in the form of microprostheses with the establishment of certain relationships correct intermaxilla. A series of experimental determinations concerning the dynamic resistance of the interposed layer between the surfaces in contact were carried out. Results: The depth of the worn layer is very small (0.3 microns) under the conditions of one million cycles, which confirms the wear resistance of ceramic materials. Conclusion: In the case of the realization of dental prostheses of small amplitude on opposing teeth, they must be made of the same material to avoid differences in resistance to breakage and abrasion. The calculated data cannot be compared with those from the specialized literature worldwide, as research in this field is very limited.